2017
DOI: 10.1093/gastro/gox005
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the medical treatment of inflammatory bowel disease among gastroenterologists

Abstract: Background and aimsWith expanding available treatment options and evolving understanding of the risks and benefits of medical therapies for inflammatory bowel disease (IBD), there is the possibility of significant variations in treatment and outcomes. Little is known about the variation in treatment between IBD specialists and other gastroenterology (GI) physicians. Evaluating possible variations is an important first step to help address standardized care and optimize treatment. We studied the differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…A lack of understanding and of the available literature has created a sense ambiguity surrounding the roles of PCPs in the management of IBD. We found gaps in the continuity of care between secondary and primary healthcare professionals; for example, issues related to the information provided to patients by healthcare professionals may be contradictory, [41][42][43]74 there can be a lack of educational tools to assist healthcare professionals in the management of patients with IBD, and there is a paucity of published literature on the primary care management of IBD. 30,71 In particular, studies showed inconsistent or variable IBD care for patients, 7,58 knowledge gaps among healthcare professionals, [41][42][43]48,54,56 a lack of guidelines for primary care practitioners to provide quality of care, 30,48 and a communication gap between patients and specialists/GPs affecting the delivery of IBD care.…”
Section: Discussionmentioning
confidence: 99%
“…A lack of understanding and of the available literature has created a sense ambiguity surrounding the roles of PCPs in the management of IBD. We found gaps in the continuity of care between secondary and primary healthcare professionals; for example, issues related to the information provided to patients by healthcare professionals may be contradictory, [41][42][43]74 there can be a lack of educational tools to assist healthcare professionals in the management of patients with IBD, and there is a paucity of published literature on the primary care management of IBD. 30,71 In particular, studies showed inconsistent or variable IBD care for patients, 7,58 knowledge gaps among healthcare professionals, [41][42][43]48,54,56 a lack of guidelines for primary care practitioners to provide quality of care, 30,48 and a communication gap between patients and specialists/GPs affecting the delivery of IBD care.…”
Section: Discussionmentioning
confidence: 99%
“…Singh et al . highlighted the variations in medication prescription within a single high‐volume center, which persists after adjusting for disease and patient characteristics . They reported that the prescription of biologics and immunomodulators is higher in IBD specialists than other general gastroenterology physicians .…”
Section: Discussionmentioning
confidence: 99%
“…11 Singh et al highlighted the variations in medication prescription within a single high-volume center, which persists after adjusting for disease and patient characteristics. 12 They reported that the prescription of biologics and immunomodulators is higher in IBD specialists than other general gastroenterology physicians. 12 In our study, the use of immunomodulators in CD and the use of biologics and immunomodulators in UC was higher at tertiary hospitals than at general hospitals/community hospitals/ clinics, whereas the use of biologics in CD was lower at tertiary hospitals than at general hospitals/community hospitals/ clinics (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations